FEASIBILITY AND ACCEPTABILITY OF A NOVEL INTEGRATION OF ABSOLUTE CARDIOVASCULAR DISEASE RISK ASSESSMENT INTO ROUTINE BLOOD CHOLESTEROL TESTING. (April 2021) - Chapman, Niamh; Fonseca, Ricardo; Murfett, Leigh; Beazley, Kevin; Mcwhirter, Rebekah; Schultz, Martin; Nelson, Mark; Sharman, James
Abstract : Objective: Absolute cardiovascular disease (CVD) risk assessment is recommended for primary prevention of CVD, yet uptake in general practice is limited. Lipid profile requests at pathology services provides an opportunity to improve uptake by integrating absolute CVD risk assessment with this service. This study aimed to assess the feasibility of such an additional service. Design and method: 299 participants (aged 45–74 years) referred to pathology services for blood cholesterol had variables required to determine absolute CVD risk measured (blood pressure, age, sex, smoking and diabetes status). Data were recorded via self-report on a computer-based application with minimal direction from staff. The absolute risk score was communicated via the report sent to the referring medical practitioner as per usual practice. Evaluation questionnaires were completed immediately post visit and at 1-, 3- and 6-month follow-up via telephone (n = 262). Results: Absolute CVD risk reports were issued for 90% of participants. Most participants (95%) reported that the length of time for the pathology service assessment was acceptable, and 91% that the self-directed computer-based application was easy to use. 78% reported a preference for pathology services to conduct absolute CVD risk assessment. Only 2% preferred a medical practitioner. Of follow-up participants, 202 (75%) had a consultation with a medical practitioner, during which, aspects of CVD risk prevention were discussed (cholesterol and blood pressure 74% and 69% of the time, respectively). Conclusions: Measurement of absolute CVD risk in pathology services is feasible, highly acceptable among middle to older adults and may increase uptake of guideline-directed care in general practice.